Frequency of Electrolyte Derangement after Transurethral Resection of Prostate: Need for Postoperative Electrolyte Monitoring - Wajahat Aziz; M. Hammad Ather (Advances in Urology)
Objective. To determine the electrolyte derangement following transurethral resection of prostate (TURP). Methods. All patients undergoing TURP from June 2012 to April 2013 were included. Preoperative electrolytes were performed within a week of procedures. Monopolar TURP using 1.5% glycine was performed. Serum Na+ and K+ were assessed within 1 hour postoperatively and subsequently if clinically indicated. Results. The study included 280 patients. Sixty-six patients (23.6%) had electrolyte derangement after TURP. Patients with deranged electrolytes were older (mean age of 73.41 ± 4.08 yrs. versus 68.93 yrs. ± 10.34) and had a longer mean resection time (42.5 ± 20.04 min versus 28.34 ± 14.64 min). Mean weight of tissue resected (41.49 ± 34.46 g versus 15.33 ± 9.74 g) and volume of irrigant used (23.55 ± 15.20 L versus 12.81 ± 7.57 L) were also significantly higher in patients with deranged electrolytes (all p=0.00). On multivariate logistic regression analysis preoperative sodium level was found to be a significant predictor of postoperative electrolyte derangement (odds ratio 0.267, S.E. = 0.376, and p value = 0.00). Conclusion. Electrolyte derangement occurs in older patients, with larger amount of tissue and longer time of resection and higher volume of irrigant, and in those with lower serum preoperative sodium levels.